2013
DOI: 10.1037/a0034373
|View full text |Cite
|
Sign up to set email alerts
|

Family income and appraisals of parental conflict as predictors of psychological adjustment and diurnal cortisol in emerging adulthood.

Abstract: The goal of the current study was to provide the first investigation of whether appraisals of parental marital conflict mediate associations of family income with emerging adult psychological adjustment and diurnal cortisol production. Participants were 178 college students who provided 3 saliva samples across the day and reported their family income, adjustment (depressive symptoms, perceived daily stress, internalizing problems, and externalizing problems), and appraisals of their parents' conflict (includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 60 publications
(127 reference statements)
6
26
0
3
Order By: Relevance
“…In addition, in emerging adulthood, self-blame for parental conflict is related to flattened diurnal cortisol production patterns (Lucas-Thompson & Hostinar, 2013). The current study adds to our knowledge by demonstrating that similar patterns are evident in adolescence and provides evidence that these flattened patterns of cortisol production linked with self-blame appear to be driven by elevated evening levels of cortisol production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, in emerging adulthood, self-blame for parental conflict is related to flattened diurnal cortisol production patterns (Lucas-Thompson & Hostinar, 2013). The current study adds to our knowledge by demonstrating that similar patterns are evident in adolescence and provides evidence that these flattened patterns of cortisol production linked with self-blame appear to be driven by elevated evening levels of cortisol production.…”
Section: Discussionmentioning
confidence: 99%
“…Broadly, stressor appraisals are critical in determining physiological responses to stressful experiences (Kemeny, 2003). The only study to investigate the role of conflict appraisals in diurnal cortisol production indicated that emerging adults who felt more self-blame for parental conflict displayed lower levels early in the day and blunted decreases in levels across the day (Lucas-Thompson & Hostinar, 2013); other appraisal dimensions (of conflict properties and threat) were not related to diurnal cortisol. However, in this study, only appraisals (and not marital conflict per se) were considered.…”
Section: Youth Conflict Appraisals As Mediators Of the Effects Of Marmentioning
confidence: 99%
See 2 more Smart Citations
“…School adjustment is a broad and multidimensional concept that is not limited to students' school performance and academic success; it also includes their affect, attitude, relationships, and involvement or engagement with the school environment (Birch and Ladd, 1997). Several studies examining school adjustment have proved that internal factors, such as individual characteristics (e.g., intelligence and emotional quotients, personality) (Ahammed et al, 2011;Warbah et al, 2007), and external factors, such as perceived stress (e.g., academic stress) (Akgun and Ciarrochi, 2003), relationships (e.g., peers) (Iwata et al, 2014) and home environment (family income and parental conflicts) (Lucas- Thompson and Hostinar, 2013;Nelson et al, 1993) have contributed to the adjustment of college students. A meta-analysis by Mattanah et al (2011) indicated that parental attachment was associated with adjustment outcomes.…”
Section: Introductionmentioning
confidence: 98%